2018
DOI: 10.32474/tceia.2018.01.000105
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Use of Nano-Silica in Concrete: A Review

Abstract: Nano-silica and its use in cement-based materials, especially concrete, has been the focus of many scientific studies. This is because cement production is an energy-intensive process and because concrete is the most used construction material worldwide. Accordingly, it is very important to understand the complexity of concrete, improve its performance and durability. This paper reviews the existing literature on the effects of nano-silica on concrete mechanical properties, microstructure and cement hydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Also, it is a cost-effective and eco-friendly material that reduces CO2 emissions. It was found that a small dosage of NS improved the early age and 28-day strength gain of GP concrete through the attributed effect, pozzolanic reaction [33] its pore-filling properties and reactive pozzolans [34]. It accelerates the polymerization rate and facilitates the development of C-S-H and N-A-S-H in natural pozzolan-based GPC [35].…”
Section: Nano Materialsmentioning
confidence: 99%
“…Also, it is a cost-effective and eco-friendly material that reduces CO2 emissions. It was found that a small dosage of NS improved the early age and 28-day strength gain of GP concrete through the attributed effect, pozzolanic reaction [33] its pore-filling properties and reactive pozzolans [34]. It accelerates the polymerization rate and facilitates the development of C-S-H and N-A-S-H in natural pozzolan-based GPC [35].…”
Section: Nano Materialsmentioning
confidence: 99%
“…4−6 In the recent past, the effects of nanosilica on cement pastes, mortars, and concrete have been investigated and it was shown that it improved the strength owing to the accelerated pozzolanic reaction, reduced porosity, and enhancement in the interfacial transition zone. 7,8 However, often the uncontrolled agglomeration and flocculation of such small particles remains a crucial issue affecting rheological and hardening behavior. Here, we have adopted a novel approach in this work.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pozzolans are primarily siliceous/aluminous substances, which themselves possess no cementitious value; however, in the presence of moisture, they chemically react with alkali hydroxide to form compounds having cementitious properties. In this regard, use of tiny silica has been found to be quite effective. In the recent past, the effects of nanosilica on cement pastes, mortars, and concrete have been investigated and it was shown that it improved the strength owing to the accelerated pozzolanic reaction, reduced porosity, and enhancement in the interfacial transition zone. , However, often the uncontrolled agglomeration and flocculation of such small particles remains a crucial issue affecting rheological and hardening behavior. Here, we have adopted a novel approach in this work.…”
Section: Introductionmentioning
confidence: 99%